Navigating the Perfect Storm: Ultrasound-Guided Peripheral Nerve Block for Emergency Amputation in a Patient with Acute STEMI and Failed PCI - Ella Priliandini; Ruddi Hartono; Ahmad Feza Fadhlurrahman; Muhammad Farlyzhar Yusuf (Archives of The Medicine and Case Reports, 2025)
Acute limb ischemia presenting concurrently with acute coronary syndrome creates a precarious clinical dilemma, often termed the "cardiac cripple" scenario. The mortality risk is compounded when patients have a history of failed percutaneous coronary intervention, severe left ventricular dysfunction, and require emergency major amputation while on active dual antiplatelet therapy. In these patients, general anesthesia poses a risk of hemodynamic collapse, while neuraxial anesthesia is contraindicated due to bleeding risks. A 75-year-old male presented with a Rutherford Grade III-IV "dead limb" of the right lower extremity and concurrent Acute Anterior STEMI (Killip II, TIMI 7/14, GRACE 137). His history included a failed percutaneous coronary intervention two months prior and three-vessel disease, resulting in a left ventricular ejection fraction of 32%. General anesthesia posed an unacceptable risk of exacerbating myocardial pump failure, while spinal anesthesia was contraindicated due to recent clopidogrel ingestion. A decision was made to perform a below-knee amputation using an ultrasound-guided femoral nerve block and a popliteal sciatic nerve block via the crosswise approach. The procedure utilized 0.5% ropivacaine with 2 mg dexamethasone. The patient remained hemodynamically stable without vasopressor support, reported a Visual Analogue Scale score of 0 intraoperatively, and avoided adverse cardiac events. In conclusion, peripheral nerve blockade, specifically the combined femoral and crosswise popliteal sciatic approach, serves as a superior anesthetic alternative in high-risk cardiac patients. It bypasses the sympatholytic risks of general anesthesia and the coagulation constraints of neuraxial techniques, offering a safe corridor for life-saving surgery.